ANALISIS KINERJA KEUANGAN INDUSTRI KREATIF DI KOTA JAMBI PASCA ACFTA DAN AIFTA - Wirmie Eka Putra; Lutfi Lutfi Lutfi (Jurnal Manajemen Terapan dan Keuangan, 2017)
This research aims to determine the difference of sales and profit levels of creative industries in Jambi City before and after the application of ACFTA and AIFTA. This research was conducted in Jambi city whose data come from creative industry actor registered as member of Dekranasda of Jambi City, coming from various creative industries in Jambi city. The creative industries in Jambi include Jambi batik handicraft, Jambi songket, wood craft, batik scrap handicraft and crafts of old and silver coin accessories. This research is designed as quantitative research with survey method to creative industry players in Jambi City. The method used in sampling this study using convenience sampling with the number of samples of 36 creative industry players. Data analysis using different test Paired sample T test. The results of this study indicate that: (1) There is a difference of creative industry sales rate in Jambi city before and after ACFTA and AIFTA, and (2) There is a difference of creative industry profit rate in Jambi city before and after ACFTA and AIFTA.